Association between microplastics and the functionalities of human gut microbiome - Bei Gao; Lixia Chen; Lizhi Wu; Shirui Zhang; Sunan Zhao; Zhe Mo; Zhijian Chen; Pengcheng Tu (Ecotoxicology and Environmental Safety)
As an integral part of humans, the gut microbiome plays a significant role in the physiological and pathological processes of the host, and dysbiosis of the gut microbiome is linked to various diseases. The impact of microplastics on the diversity and composition of human gut microbiome has been reported previously. However, effects of microplastics on the functionality of the gut microbiome in humans have not been well studied. In the present study, concentrations of microplastics in human blood were detected through pyrolysis-gas chromatography/mass spectrometry in 39 adults. Five types of microplastics were found in human blood, including polyvinyl chloride, polyethylene, polypropylene, polystyrene, and polyamide 66. Shotgun metagenomic sequencing was further employed to analyze the metagenomes of the human stool samples and fecal samples from mice exposed to microplastics. Associations were found between microplastics and microbial species, as well as microbial genes encoding invasion-related virulence factors, quorum sensing, autoinducer and transporter system, and microplastic biodegradation enzymes. The findings are of significance to improve the understanding of functional changes in the gut microbiome associated with microplastic exposure, as well as raising awareness regarding the health risks of microplastics in the human population.